The structure of solid adsorbent for alternative fuel composition - Бутенко, Анатолий Николаевич; Юрченко, Анна Александровна; Блинков, Николай Андреевич (Technology audit and production reserves, 2013)
This article considers the production of new fuel composition using the new structure of adsorbent for the dehydration of ethanol. The main objectives of this study is to develop the adsorbent structure for the new fuel composition, being able to replace conventional gasoline in internal combustion engines, and thus capable of efficient regeneration for unlimited and multiple using; as well as to efficiently absorb water and thus almost not to be subjected to hydrolysis in order not to form the alkali which dissolves in ethanol and causes corrosion of the engine. The effectiveness of the new fuel composition has been tested in experimental internal combustion engine and then the energy efficiency of the new fuel composition has been determined which constitutes 75% of the energy efficiency of conventional gasoline. The new adsorbent composition has been developed which is capable of regenerating while a slight heating in vacuum to its original state, and efficient dehydration of ethanol. On the basis of water-free ethanol by adding 15% gasoline a new fuel composition has been created that can successfully replace conventional gasoline and significantly reduce the energy dependence of Ukraine on imports of conventional fuels.